A new skink of the genus Subdoluseps Freitas, Datta-Roy, Karanth, Grismer & Siler, 2019 (Squamata: Scincidae) from southern Vietnam - Le, Manh Van; Nguyen, Vu Dang Hoang; Phan, Hoa Thi; Rujirawan, Attapol; Aowphol, Anchalee; Vo, Thi-Dieu-Hien; Murphy, Robert W.; Nguyen, Sang Ngoc (Zootaxa, 2021)
We describe a new species of the genus Subdoluseps Freitas, Datta-Roy, Karanth, Grismer & Siler from a coastal area in southern Vietnam. Subdoluseps vietnamensis sp. nov. is characterized by the following morphological characters: medium size in adults (snout-vent length up to 48.7 mm); tail length/snout-vent length ratio 1.04; toes not reaching finger when limbs adpressed; 27–30 midbody scale rows, smooth; 55–57 paravertebral scales; 55–62 ventral scale rows; 64–74 subcaudal scales; frontoparietal scale single; four supraoculars; prefrontals not in contact with one another; two loreal scales; seven supralabials; ear-opening with two lobules on the anterior border; smooth lamellae beneath finger III 9 or 10 and toe IV 12–15; six enlarged precloacal scales; and four distinct black stripes on dorsum. The new species differs genetically from its closest congeners, S. bowringii (Günther) and S. frontoparietale (Taylor), by uncorrected p-distances of 10.0% and 9.5%, respectively in ND1 sequences, and clusters into the same matriline with these two congeners on the phylogenetic trees.